Botswana's Infrastructure : A Continental Perspective - Briceno-Garmendia, Cecilia; Pushak, Nataliya (2012)
Infrastructure made a net contribution of just over two percentage points to Botswana's improved per capita growth performance in recent years. Raising the country s infrastructure endowment to that of the region's middle-income countries could boost annual growth by about 1.2 percentage points. Botswana has made significant infrastructure progress in recent years, spanning the transport, water and sanitation, power, and mobile telephony sectors. But the country still faces a number of important infrastructure challenges. The most pressing is in the power sector, where the country is economically and financially exposed to a lack of generation capacity and insufficient power supply, leaving the economy vulnerable to power price shocks and load shedding. Botswana's international transport connections and Internet connectivity also lag behind those of comparable countries. Botswana's overall resource envelope of $800 million per year surpasses its $785 million needs estimate. Nevertheless, it loses $68 million a year to inefficiencies and faces a funding gap of $305 million per year, entirely in the power sector, traceable to the quality of spending decisions. Botswana will be in a good position to meet its infrastructure goals if it can reduce inefficiencies, increase public-sector receipts, and attract more public funding.